Dekonstruksi Konsep Nafkah: Analisis Systematic Literature Review terhadap Keadilan Gender dalam Rumah Tangga Muslim - Hermanto, Rendy Dwi; Subhan, Ahmad (Jurnal Antologi Hukum, 2025)
The concept of nafkah (spousal maintenance) in classical fiqh is generally understood as the sole obligation of the husband, reinforcing male dominance within the household structure. This view is rooted in normative interpretations shaped by a patriarchal context, which tend to overlook contemporary social dynamics and the active economic role of women in family life. This article seeks to re-examine the legal construction of nafkah through a Systematic Literature Review (SLR) of both classical and contemporary fiqh literature, with particular emphasis on integrating the principles of maqasid al-shari‘ah and gender justice perspectives. The findings reveal that classical fiqh structurally reproduces gender inequality through textual readings that lack contextual sensitivity. In contrast, the thought of contemporary Muslim scholars and academics offers more egalitarian approaches, emphasizing collaboration and justice in household relations. This study recommends revising the fiqh al-munakahat curriculum, reforming Islamic family law regulations, and updating fatwas to be more responsive to social change. Thus, a reinterpretation of the concept of nafkah can contribute to the development of a more just, inclusive, and contextually relevant Islamic legal system.